Tryptophan auxotrophs of Rhizobium japonicum. - Wells, S E (1983)
Eleven tryptophan-requiring mutants of Rhizobium japonicum I-110 ARS were isolated after nitrous acid mutagenesis and fell into five groups based on characterization by supplementation with intermediates and enzyme assays.